Regional Trade Arrangements in Africa : Past Performance and the Way Forward - Yang, Yongzheng (IMF Working Papers; Working Paper ;, 2005)
Regional trade arrangements (RTAs) in Africa have been ineffective in promoting trade and foreign direct investment. Relatively high external trade barriers and low resource complementarity between member countries limit both intra- and extraregional trade. Small market size, poor transport facilities and high trading costs make it difficult for African countries to reap the potential benefits of RTAs. To increase regional trade and investment, African countries need to undertake more broad-based liberalization and streamline existing RTAs, supported by improvements in infrastructure and trade facilitation. Early action to strengthen the domestic revenue base would help address concerns over revenue losses from trade liberalization.